2022
DOI: 10.7341/20221825
|View full text |Cite
|
Sign up to set email alerts
|

Employee retention through effective human resource management practices in Maldives: Mediation effects of compensation and rewards system

Abstract: PURPOSE: The purpose of this study is to examine the effects of human resource management (HRM) practices on employee retention mediated by reward and compensation. Also, this study has examined the moderating role of performance appraisal, and training and development on the relationship between HRM practices and employee retention. METHODOLOGY: A sample of 250 respondents among the employees working in the retail sector in Capital City of Maldives was selected using the random probability sampling technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…Lastly, H6 investigated the impact of compensation and rewards on employee retention. The results showed a significant relationship (β = 0.104, t = 1.945, P < 0.016), supporting previous research highlighting the influence of fair and satisfactory compensation and rewards on employee retention (Hassan, 2022). Hence, H6 is accepted.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lastly, H6 investigated the impact of compensation and rewards on employee retention. The results showed a significant relationship (β = 0.104, t = 1.945, P < 0.016), supporting previous research highlighting the influence of fair and satisfactory compensation and rewards on employee retention (Hassan, 2022). Hence, H6 is accepted.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Studies conducted in Maldives have demonstrated that positive perceptions of career development practices significantly and positively affect employee retention (Imna et al, 2015). Similarly, a substantial body of research supports the notion that enhancing career growth opportunities leads to higher employee retention rates (Hassan, 2022). Conversely, some studies have found that poor implementation of career growth practices within organizations significantly increases employee turnover intention (Manthi et al, 2018).…”
Section: Career Growth As Moderator Between Job Performance Job Satis...mentioning
confidence: 98%
See 3 more Smart Citations